2022
DOI: 10.1002/anie.202208150
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytically Stable Ionic Fluorogels for High‐Performance Remediation of Per‐ and Polyfluoroalkyl Substances (PFAS) from Natural Water

Abstract: PFAS are known bioaccumulative and persistent chemicals which pollute natural waters globally. There exists a lack of granular sorbents to efficiently remove both legacy and emerging PFAS at environmentally relevant concentrations. Herein, we report a class of polymer networks with a synergistic combination of ionic and fluorous components that serve as granular materials for the removal of anionic PFAS from water. A library of Ionic Fluorogels (IFs) with systematic variation in charge density and polymer netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…This affinity for fluorocarbons is characteristic of fluorinated compounds and can leverage distinct binding mechanisms for molecules like PFAS. The concept of employing fluorinated compounds for PFAS capture has been previously reported. For example, highly fluorinated porous cyclodextrin polymers were found to remove PFOA at environmentally relevant concentrations . Moreover, PFOA has been captured at high capacities by fluorine-rich calix[4]-arene-based porous polymers due to favorable CF···FC interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This affinity for fluorocarbons is characteristic of fluorinated compounds and can leverage distinct binding mechanisms for molecules like PFAS. The concept of employing fluorinated compounds for PFAS capture has been previously reported. For example, highly fluorinated porous cyclodextrin polymers were found to remove PFOA at environmentally relevant concentrations . Moreover, PFOA has been captured at high capacities by fluorine-rich calix[4]-arene-based porous polymers due to favorable CF···FC interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PFOA has been captured at high capacities by fluorine-rich calix[4]-arene-based porous polymers due to favorable CF···FC interactions . Recent studies have also included short-chain PFAS like perfluorobutanoic acid (PFBA) and hexafluoropropylene oxide-dimer acid (GenX), using ionic fluorogels and magnetic fluorinated polymers, showing larger removal efficiencies compared to nonfluorinated versions of the sorbents. However, the removal efficiency decreased significantly with a decreasing chain length of the PFAS despite showing higher sorption capacities than nonfluorinated sorbents. Furthermore, there are a range of unanswered questions regarding the molecular mechanisms in which fluorinated sorbents bind short-chain PFAS and the extent to which fluorophilic interactions impact PFAS binding.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that adsorbents with cationic groups or fluorocarbon chains ,, interact strongly with the respective components of PFAS adsorbates (Figure a). This strategy has borne fruit in the design of PFAS-selective COFs.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of PFOA to soil concentrations above 800 mg L –1 caused cellular damage in the roots, stems, and leaves of wheat seedlings and inhibited wheat growth. , This is due to the ecotoxicity of PFOA resulting in reduced growth and biomass, disruption of chlorophyll accumulation, and soluble protein synthesis in wheat roots and leaves. In particular, PFOAs in food crops pose a possible risk to human health since they ultimately end up transferring poisons to humans, either directly or indirectly. …”
mentioning
confidence: 99%